PERFORMANCE OF Pongamia pinnata – Costus igneus SILVI-MEDICINALAGROFORESTRY SYSTEM UNDER SEMI-ARID ALFISOLS - A. MADHAVI LATA and ASHLY (The Journal of Research, PJTSAU, 2026)
A field experiment entitled “Integrated nutrient management studies in Pongamia + Insulin (Costus igneus)silvi-medicinal system” was conducted during kharif, 2018 at Students Farm, Professor Jayashankar Telangana StateAgricultural University campus, Rajendranagar, Hyderabad, Telangana. The soil of the experimental site was sandy loam with apH (7.34), EC (0.48 dS m-1) and organic carbon (0.29%). Soil was low in available nitrogen (148.98 kg ha-1) and medium inavailable phosphorus (59.14 kg ha-1) and potassium (286.68 kg ha-1). The experiment was laid out in Randomized block designwith three replications and nine treatments viz.,T1 Control (no fertilizer and manure), T2 100% RDF (75:50:50 NPK), T3 75% RDN + 25% N through neem cake, T4 75% RD N + 25% N through Biochar, T5 75% RD N + Pongamia green leaf manure @10 t ha-1, T6 50% RD N + 50% N through neem cake, T7 50% RD N + 50% N through Biochar, T8 50% RD N + Pongamia green leaf manure@10 t ha-1 and T9 Sole insulin crop without trees. Results showed that Gross monetary returns (¹ 78024 ha-1) and net monetaryreturns (¹ 47575 ha-1) were higher with 50% RD N + 50% N through neem cake followed by 50% RD N + PGLM @10 t ha-1.However, B:C ratio was highest in 50% RD N + PGLM @10 t ha-1 due to the low cost of cultivation incurred. From the presentinvestigation, it can be concluded that, among nutrient management practices tested, 50% RD N + 50% N through neem cake (T6)and 50% RD N + PGLM @10 t ha-1 (T8) in silvi-medicinal system was better for realizing higher yields and economic returns apartfrom sustaining better available nutrient status in soil.